Spontaneous Adrenal Hemorrhage in Pregnancy: A Case Series. (22nd March 2017) - Gupta, Ankita; Minhas, Ruby; Quant, Hayley S.
Abstract : Background . Abdominal pain during pregnancy has a broad differential diagnosis which includes spontaneous adrenal hemorrhage (SAH). There is scant literature available on optimal mode of delivery in stable patients. Cases . Patient 1 was a 35-year-old nullipara who presented at 36 weeks of gestation with left flank pain. Patient 2 was a 27-year-old multipara at 38 weeks who presented with left upper quadrant pain. Diagnosis of SAH was made by CT scan and both were managed with pain control, serial hemoglobin assessments, and abdominal exams resulting in uncomplicated vaginal deliveries. Conclusion . SAH, although rare, is an important consideration when evaluating abdominal and flank pain in pregnancy. Management options vary from conservative management to surgical intervention depending on the stability of the patient.